Mobile displays : technology and applications. - Bhowmik, Achintya K., ....-; Bos, Philip J., ....-; Li, Zili, ....- (Chichester : Wiley, 2008)
This book provides a comprehensive, systematic and up-to-date overview of the existing and emerging mobile display technologies for use in a large number of applications, such as mobile telephones, PDAs and portable computers. Experts on mobile display technology from both academia and industry have contributed chapters on the design considerations and technical requirements of mobile displays, as well as advances in LCD technologies for mobile displays and advances in mobile displays interfaces. The book also covers emerging mobile display technologies such as organic light-emitting displays (OLEDs), carbon nanotube field emission displays (FEDs), plastic backplanes, electronic ink and also 'beyond direct-view' technologies, including projection displays and eye-ware displays.